2000
DOI: 10.2527/2000.7871738x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ruminal biohydrogenation on the feeding value of fat in finishing diets for feedlot cattle.

Abstract: Four Holstein steers (212 kg) with cannulas in the rumen and proximal duodenum were used in a 4 x 4 Latin square experiment to study the influence of degree of ruminal biohydrogenation (BH) on the feeding value of supplemental fat. Treatments consisted of an 88% concentrate finishing diet supplemented with 1) 2% yellow grease (control); 2) 4% formaldehyde-protected fat (Rumentek), 2% yellow grease (LBH); 3) 2% Rumentek, 4% yellow grease (MBH); or 4) 6% yellow grease (HBH). Ruminal BH of HBH, MBH, and LBH diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 36 publications
8
57
0
20
Order By: Relevance
“…Our results agree with those of Zinn et al (2000) who reported higher post-ruminal digestibility of all C 18 FA when steers were fed yellow grease. In contrast, several researchers reported reduction in post-ruminal digestibility of individual unsaturated C 18 FA as a result of soybean or canola seed supplementation (Tice et al 1994;Hussein et al 1996).…”
Section: Intakes and Flows Of Fasupporting
confidence: 92%
“…Our results agree with those of Zinn et al (2000) who reported higher post-ruminal digestibility of all C 18 FA when steers were fed yellow grease. In contrast, several researchers reported reduction in post-ruminal digestibility of individual unsaturated C 18 FA as a result of soybean or canola seed supplementation (Tice et al 1994;Hussein et al 1996).…”
Section: Intakes and Flows Of Fasupporting
confidence: 92%
“…Isto também foi constatado por Ngidi et al (1990), que observaram que o uso de sais de cálcio de ácidos graxos nos níveis de 0 até 6% da matéria seca, para engorda de novilhos, não influenciou a espessura de gordura da carcaça ou a área de olho de lombo. Resultado semelhante foi observado por Zinn et al (2000), que alimentaram novilhos holandeses com dietas de sais de cálcio de ácidos graxos e gordura animal, até o nível de 6% e concluíram que estas dietas não tiveram efeito sobre a área de olho de lombo ou sobre a gordura subcutânea.…”
Section: Resultsunclassified
“…However, this inhibition may also be attributed to the level of dietary fat, and the optimal levels of unsaturated fatty acids in the diet are unknown. Some authors, such as Zinn et al (2000), Weiss & Pinos-Rodriguez (2009) and Hess et al (2008), report that levels higher than 50 and 60 g lipids/kg of DM in DM fat supplements affect the DM intake, while others, such as NRC (2001) Ueda et al (2003), and Harvatine & Allen (2006), report that up to 30 g lipids/kg of DM diet can be used with minimal negative effects on microbial growth and rumen function. These results indicated that the effects of unsaturated fatty acids on ruminal fermentation could be variable because of the lipid levels and basal diet composition.…”
Section: Introductionmentioning
confidence: 99%